1996
DOI: 10.1088/0031-9155/41/1/006
|View full text |Cite
|
Sign up to set email alerts
|

Domestic magnetic field exposures in Avon

Abstract: To define a protocol for surrogate measurement of magnetic field exposure by questionnaire, a series of spot and 24-hour measurements was made at 50 houses in Avon, UK. Measurements were made with Emdex II equipment in the centres of rooms with the house power encountered at the start of the visit, and then with all power to the house isolated at the main switch. The mean spot magnetic field averaged over the 50 homes for each room varied between 0.011 and 0.023 microT with an overall mean (0.017 +/- 0.003) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
1
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 17 publications
5
30
1
2
Order By: Relevance
“…The distribution is strikingly close to log normal, with a geometric mean of 0.032 µT, and a retransformed standard deviation of 0.031 µT. The mean phase I exposure level falls between the geometric mean levels of 0.029 and 0.037 µT, published previously for UK homes (Merchant et al, 1994a(Merchant et al, , 1994bPreece et al, 1996;Swanson and Kaune, 1999). The residential and school components of the total exposure have a similar distribution.…”
Section: Phase I Measurementssupporting
confidence: 72%
“…The distribution is strikingly close to log normal, with a geometric mean of 0.032 µT, and a retransformed standard deviation of 0.031 µT. The mean phase I exposure level falls between the geometric mean levels of 0.029 and 0.037 µT, published previously for UK homes (Merchant et al, 1994a(Merchant et al, , 1994bPreece et al, 1996;Swanson and Kaune, 1999). The residential and school components of the total exposure have a similar distribution.…”
Section: Phase I Measurementssupporting
confidence: 72%
“…power transmission lines, Wertheimer et al, 1979;Savitz et al, 1988;Preston-Martin et al, 1996;Michaelis et al, 1997b). For the majority of people, however, indoor sources account for most of the exposure (Preece et al, 1996;Schu¨z et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Preece et al [1996] surveyed a sample from a cohort of mothers with surviving children and found no one-bedroom homes and 24% four-bedroom homes. This finding represents a bias toward large homes compared with the national housing stock.…”
Section: Factors Affecting the Results Of Measurements Sample Selectionmentioning
confidence: 99%
“…Silva et al [1989] reported 5-15%; Kaune et al [1987] reported an upper boundary of 24%; Zaffanella [1993] reported 10% or less in 90% of measurements in a subset of the sample; and Preece et al [1996] reported 15% in kitchens. In principle, the result of a field measurement will depend on whether the meter used is sensitive to harmonics or not.…”
Section: Harmonicsmentioning
confidence: 99%